KEWIRAUSAHAAN SOSIAL BERBASIS PEMBERDAYAAN PEREMPUAN DALAM MENINGKATKAN EKONOMI LOKAL - Siti Rohmah (Department of Islamic Community Development, Faculty of Da'wah, State Islamic University (UIN) of Sultan Maulana Hasanuddin Banten, 2019)
Women today have quite diverse roles, from educator to career. Currently they have various roles that can contribute to provide for family income. This research aims; 1) to identify the social entrepreneurship based on women’s empowerment through woven pandanus training, 2) to analyze the supporting factors and obstacles ocial entrepreneurship based on women’s empowerment through woven pandanus training. In this study used qualitative methods and data collection techniques using observation, interview, and documentation. Based on research that has been done, it can be concluded that social entrepreneurship based on women’s empowerment this uses several, stages preparation phase, assessment stage, alternative planning stage of the program or activity, the stage of formulation of the action plan, the stage of implementation and assistance, the evaluation phase, the termination stage. Women taught how to make crafts by utilizing the potential of the natural surroundings, namely pandanus leaves which can made into items that have sale value such as mats, hats, player mats and bags. Furthermore, the supporting factors in the empowerment activities through this craft and woven training, there is collaboration between Pandan’s Craft and the agency/company. Finally, the inhibiting factors such as the low human resources and lack of curiosity.